Performance of Chromium Exchanged Zeolite Catalysts In The Combustion Of Volatile Organic Compound Pollutants - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (De La Salle University Press Inc, 2004)
The activity and stability of chromium exchanged beta (Cr BEA), mordenite (Cr-MOR) and ZSM-5 (Cr-ZSM-5) zeolites of different Si/Al ratios for volatile organic compounds (VOCs) combustion are reported.